Towards to secure an IoT adaptive environment system - Oliveira, Pedro Filipe (2020)
This paper, deals with the actual problem of secure an IoT adaptive system, namely using secure techniques to secure a Smart Environment System, and the privacy of their users. On a new era of interaction between persons and physical spaces, users want that those spaces smartly adapt to their preferences in a transparent way. This work wants to promote a balanced solution between the need of personal information and the user’s privacy expectations. We propose a solution based on requiring the minimal information possible, together with techniques to anonymize and disassociate the preferences from the users.